Understanding communication style of politics Ganjar as Governor to DPRD Jateng - Ralp Johnson Batubara Johnson Batubara; Nuriyatul Lailiyah, S.I.Kom, M.I.Kom (Interaksi Online, 2017)
Currently the communication style leaders in Indonesia in the spotlight to show the image of the political communicator. The style of political communication is a hallmark of which is owned by the communicator. In any government, political communication style of political communicator affect relationships within the government's performance. In this case Ganjar as governor has its own style of political communication in communicating with the parliament of Central Java. The problem in this research is the emergence of the problems that occur through Ganjar political communication style in communicating with the local parliament in the highlight of the media, so that the public feel there is turmoil in local government. This research method using a qualitative approach with case study method. The case study uses several methods to collect data that interviews and observations and secondary data supporting examine the case in detail. Researchers conducted interviews with six members of parliament representative of the five commissions and five different fractions. Interviews were conducted in-depth interviews and results in reduction as well as in categorizing. After the primary data collected then the contents of the data that has been categorized discussed and analyzed. In the analysis of these data, the researchers classify into two aspects that have an influence on the style of political communication Ganjar, the technical aspects are divided into verbal and nonverbal communication as well as the substantive aspects were also divided into two political messages and communication links and Ganjar Parliament The results of the analysis revealed that the style of political communication Ganjar do have a tendency for low-style context. As well as that impede communication ganjar and Parliament is an aggressive style and bombastic style.